Institutional Factors Affecting Quality of Documentation of Nursing Care in Selected County Referral Hospitals in Kenya - Mukuna, Anne; Mwaura-Tenambergen, Wanja; Njoroge, Kezia (International Journal of Professional Practice, 2025)
Nurses are responsible for continuous patient care. The proof of care activities is through documentation. Several studies have shown serious shortcomings in nursing care documentation. This study sought to determine the institutional factors that affect the quality of nursing care documentation. It was a descriptive survey, carried out in three County Referral Hospitals; Isiolo, Nyeri and Nyandarua in Kenya. The target population was nurse managers, and nurses in the selected hospitals, and patient case files in the medical surgical units of the sampled hospitals. Multistage technique was used to sample 88 nurses, 6 nurse managers, and 158 patient case files. Data was collected using a questionnaire and key informant guide. Themes and content analysis were used for qualitative data, while quantitative data were analyzed using regression analysis with SPSS (version 26.0). Findings were presented using frequency tables and charts. The results revealed only one-third (35.4%) of nursing care documentation practices were done well. Factors identified to influence nursing care documentation include existence of standard operating procedures on nursing care documentation, a high patient load per shift, and institutional culture on nursing documentation. Regression analysis demonstrated a positive relationship between the institutional factors, presence of SoPs, and institutional culture, with bivariate logistic regression scores of 1.335, 1.133, and 1.026 respectively. This association was not statistically significant, pointing to existence of confounding factors. This implies that improvement efforts must be made to identify and address other key process determinants. The study concludes that improvement of nursing care documentation practice requires identification and address of the multiple factors that affect the nursing practice. Health facility management is recommended to ensure that nurses have access to nursing documentation practices SOPs; to organize CPD sessions on nursing documentation; to build a positive culture on nursing documentation practices; and to adhere to the recommended nurse-patient ratios.